Clinical application of serum alpha-fetoprotein-IgM complexes on the diagnosis of primary hepatocellular carcinoma in Kazakh and Han populations. Issue 4 (July 2013) - Wu, Jun; Zou, Han; Jiang, Jing-Ting; Li, Xiao-Dong; Zhao, Xue-Mei; Jar, Ken; Wang, Hong; Xu, Bin; Wu, Chang-Ping
Aims and background: We detected serum AFP-IgM levels in patients with primary hepatocellular carcinoma in Kazakh and Han populations to investigate the clinical significance of AFP-IgM in the diagnosis of hepatocellular carcinoma. Methods and study design: Serum AFP-IgM levels were examined in 28 cases of hepatocellular carcinoma and 164 controls in the Kazakh population and in 85 cases of hepatocellular carcinoma and 187 controls in the Han population. AFP-IgM was detected with the ELISA assay. Results: In general, serum AFP-IgM levels of hepatocellular carcinoma patients in the Han population and hepatocellular carcinoma patients in the Kazakh population were statistically higher than those of controls, but there was no statistical significance between hepatocellular carcinoma patients in the Han and hepatocellular carcinoma patients in the Kazakh population. Conclusions: AFP-IgM is an encouraging serological marker and may be useful in the diagnosis of hepatocellular carcinoma.